2023
DOI: 10.1186/s13578-023-01078-4
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota-derived tryptophan metabolites alleviate liver injury via AhR/Nrf2 activation in pyrrolizidine alkaloids-induced sinusoidal obstruction syndrome

Abstract: Background and aims Hepatic sinusoidal obstruction syndrome (HSOS) is caused by toxic injury, such as pyrrolizidine alkaloids, to the liver sinusoidal endothelial cells, and the gut microbiota may be involved. However, the specific role and underlying mechanism of gut microbiota in HSOS is unknown. Methods HSOS model was established by gavage of monocrotaline (MCT) in rats. Fecal microbiota transplantation (FMT) with HSOS-derived or healthy gut flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The gut microbiota is believed to play a crucial role in the development of various acute and chronic liver diseases, e.g., (non-)alcoholic liver disease, hepatitis virus infection, and chemical-or drug-induced liver injuries [75]. One of the potential causes of hepatotoxicity is gut dysbiosis and microbial metabolites.…”
Section: Various Susceptibility To Pasmentioning
confidence: 99%
See 1 more Smart Citation
“…The gut microbiota is believed to play a crucial role in the development of various acute and chronic liver diseases, e.g., (non-)alcoholic liver disease, hepatitis virus infection, and chemical-or drug-induced liver injuries [75]. One of the potential causes of hepatotoxicity is gut dysbiosis and microbial metabolites.…”
Section: Various Susceptibility To Pasmentioning
confidence: 99%
“…Due to the insufficient microbiome-derived tryptophan metabolism within the gut lumen resulting in decreased activity of AhR (aryl hydrocarbon receptor)/Nrf2 (nuclear transcription factor) signaling in the liver, HSOS was induced by the applied PA. The suggested therapeutic approach for treating the PA-induced HSOS is to restore or enrich the population of specific bacteria by supplementation with specific tryptophan metabolites (AhR ligands), or to directly administer with pharmacological AhR agonists [75].…”
Section: Various Susceptibility To Pasmentioning
confidence: 99%
“…Evidence has revealed that the microbiota in PA-HSOS animals is different from that of healthy individuals, and the abundance of potentially pathogenic bacteria is significantly increased. 19 , 20 However, the involvement of the gut bacterial flora in the development of PA-HSOS has not been fully elucidated, particularly short-chain fatty acids (SCFAs), which are thought to mediate the health benefits of the intestinal microbiome. In this study, we observed gut microbiota dysbiosis and impairment of the gut barrier in PA-HSOS patients and mice and that gut microbiota dysbiosis further resulted in enhanced M1 macrophage polarization via alteration of intestinal barrier function mediated by butyrate, aggravating the progression of PA-HSOS.…”
Section: Introductionmentioning
confidence: 99%